The Economic, Social and Political Elements of Climate Change - Leal Filho, Walter; SpringerLink; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg Imprint: Springer, 2011)
A unique feature of this book is its strong practice-oriented nature: it contains a wide range of papers dealing with the social, economic and political aspects of climate change, exemplifying the diversity of approaches to climate change management taking place all over the world, in a way never seen before. In addition, the book describes a number of projects and other initiatives happening in Africa, Asia, Europe, Latin American and the Australasian region, providing a profile of the diversity of works taking place today.(P)
The Economic, Social and Political Elements of Climate Change; Foreword; Contents; Part I: Social Aspects of Climate Change; Part II: Economic Aspects of Climate Change; Part III: Political Aspects of Climate Change; Part IV: Practical Aspects, Initiatives, Frameworks and Projects; About the Authors; Index.
Electronic reproduction.
Keywords: Climatic changes -- Economic aspects -- Congresses; Climatic changes -- Social aspects -- Congresses; Climatic changes -- Political aspects -- Congresses; Electronic books